Case report: A late-onset cobalamin C defect first presenting as a depression in a teenager - Cheng, Siqi; Chen, Weihong; Zhao, Mingmin; Xing, Xing; Zhao, Lei; Ren, Bowen; Li, Na (Frontiers in Genetics, 2022)
Background: The Cobalamin C (cblC) defect, a common inborn disorder of cobalamin metabolism due to a genetic mutation in MMACHC, can cause combined methylmalonic acid and homocysteine accumulation in blood, urine, or both. In this paper, a late-onset case was reported, and the patient firstly presented with depression identified with the MMACHC gene. We summarized the clinical feature of the cblC defect, the relationship between genotype and phenotype, and the clinical experience concerning the diagnosis and treatment procedure of cblC defect. Case presentation: Initially presented with depression, the 16-year-old female patient showed progressive abnormal gait and bilateral lower limb weakness after 3 months. Blood routine examination suggested severe hyperhomocysteinemia, and screening for urine organic acids found elevated methylmalonic acid. Family gene sequencing showed mutations detected in MMACHC. She had a compound heterozygous mutation, while the c.271dupA (p.R91Kfs＊14) was only detected in her father and the c.482 G>A (p.R161Q) was only detected in her mother. Hence, she was diagnosed with cblC defect and treated by B vitamins supplement. The muscle strength of both lower limbs was obviously improved. Conclusions: This case indicated that depression could be a presenting sign of cblC-type methylmalonic aciduria and homocysteinemia, and enhanced the genotype-phenotype relationship of cblC defect, which will contribute to further understanding of this emerging disease.